Doing mandir, doing kōvil: Eine empirische Rekonstruktion hinduistischer Tempelpraktiken in der Schweiz und in Österreich - Limacher, Katharina (Religionen aktuell, 2021)
This detailed study in religious studies is intended as a contribution to the study of Hinduisms. It reconstructs Hindu temple practices in Zurich and Vienna, representative of two national contexts. The focus is on the question of the practical execution of events in the Hindu temple, i.e. the question of which practices create a temple as such. Committed to an ethnomethodological approach, the study reconstructs the routine of communal Hindu temple practice - the 'doing mandir'. In doing so, it fills a research gap and contributes to the establishment of practice theory approaches in religious studies and their translation into the concretion of empirical research